2000
DOI: 10.1159/000020664
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intrarenal Endothelin 1, Endothelin 3, and Angiotensin II Expression in Chronic Cyclosporin A Nephrotoxicity in Rats

Abstract: Endothelin 1 (Et1) is widely expressed in the kidney and is related to several functions and to pathological conditions with progression towards sclerosis. The function of endothelin 3 (Et3) at the renal level is debatable, but it could have an important regulatory function in the reabsorption of water through its action on tubular type B receptors. Angiotensin II has recently been implicated as the principal factor responsible for the progression of interstitial fibrosis induced by cyclosporin A (CsA). We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Several mechanisms have been proposed in cyclosporineinduced nephrotoxicity, namely, the activation of the reninangiotensin system and enhanced sympathetic tone (Dell et al, 2003), increased synthesis of endothelin (Ramirez et al, 2000), inductions of cytochrome P450 enzymes in renal microsomes (Serino et al, 1994), and renal vasoconstriction attributed to an imbalance in releasing of the vasoactive substances, including reduction of vasodilator factors in particular nitric oxide (Yoon et al, 2009). Other studies have clearly demonstrated that cyclosporine-induced oxidative stress plays a pivotal role in producing structural and functional impairment of the kidney (Burdmann et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Several mechanisms have been proposed in cyclosporineinduced nephrotoxicity, namely, the activation of the reninangiotensin system and enhanced sympathetic tone (Dell et al, 2003), increased synthesis of endothelin (Ramirez et al, 2000), inductions of cytochrome P450 enzymes in renal microsomes (Serino et al, 1994), and renal vasoconstriction attributed to an imbalance in releasing of the vasoactive substances, including reduction of vasodilator factors in particular nitric oxide (Yoon et al, 2009). Other studies have clearly demonstrated that cyclosporine-induced oxidative stress plays a pivotal role in producing structural and functional impairment of the kidney (Burdmann et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Recent clinical studies in elderly patients with atherosclerotic vascular disease suggested, in fact, that excessive angiotensin II inhibition in kidneys that are vascularly compromised may have detrimental effects (33). Conversely, experimental models of CsA-induced interstitial fibrosis have shown that CsA renal toxic effects are mediated in part by angiotensin II and that, despite more pronounced renal hypoperfusion, the addition of an ACEI to CsA limits tubulointerstitial changes (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies of a model of chronic cyclosporin A toxicity in rats revealed intrarenal deposits of Ang II, which increased with time (del Moral et al, 1997). Increased expression of Ang II was observed in the outer medulla and medullary rays in rats treated with cyclosporin A (Ramírez et al, 2000).…”
Section: Angiotensin Ii-dependent Hypertensive Models a Angiotensinmentioning
confidence: 94%